2000
DOI: 10.1046/j.1365-2141.2000.02128.x
|View full text |Cite
|
Sign up to set email alerts
|

Activated protein C inhibits lipopolysaccharide‐induced nuclear translocation of nuclear factor κB (NF‐κB) and tumour necrosis factor α (TNF‐α) production in the THP‐1 monocytic cell line

Abstract: Summary. Activated protein C (APC) protects against sepsis in animal models and inhibits the lipopolysacharide (LPS)-induced elaboration of proinflammatory cytokines from monocytes. The molecular mechanism responsible for this property is unknown. We assessed the effect of APC on LPS-induced tumour necrosis factor a (TNF-a) production and on the activation of the central proinflammatory transcription factor nuclear factor-kB (NF-kB) in a THP-1 cell line. Cells were preincubated with varying concentrations of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
165
2
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(177 citation statements)
references
References 25 publications
6
165
2
1
Order By: Relevance
“…Although ILs 10 and 12p70 were assayed with the CBA, no treatment group expressed either cytokine at concentrations exceeding 10 pg/ml (data not shown). We also observed a minor but significant 8% down-regulation of THP-1 TNF expression by 120 nM activated protein C. Such a small effect may appear inconsistent with previously published results that revealed inhibitions exceeding 50% (14). However, activated protein C concentrations in these previous studies exceeded 3.6 M, representing a probable cause for this discrepancy.…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…Although ILs 10 and 12p70 were assayed with the CBA, no treatment group expressed either cytokine at concentrations exceeding 10 pg/ml (data not shown). We also observed a minor but significant 8% down-regulation of THP-1 TNF expression by 120 nM activated protein C. Such a small effect may appear inconsistent with previously published results that revealed inhibitions exceeding 50% (14). However, activated protein C concentrations in these previous studies exceeded 3.6 M, representing a probable cause for this discrepancy.…”
Section: Discussioncontrasting
confidence: 90%
“…sepsis receiving recombinant activated protein C contained reduced levels of IL-6 (4). In vitro studies have also revealed that 360 nM and 3.6 M activated protein C inhibited TNF-␣ secretion by CD14 ϩ peripheral monocytes and by THP-1 cells, respectively (14,15). However, the regulated secretion of numerous other cytokines by activated protein C-treated monocytes has not been documented to date.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…NF-κB is activated by LPS in THP-1 cells, the transcription factor NF-kB is associated with metabolic and inflammatory responses, including nuclear receptors, activators of protein (AP-1) and early growth response (EGR). Furthermore, it is suggested that IKK/NF-kB is a target for the treatment of periodontitis disorders (White et al, 2000;Carpenter andO'Neill., 2007, Chen, 2007). As it was believed that the expression of NF-kB (p50/p65) affects the occurrence of aggressive and chronic periodontitis, this study revealed observations of its expression in patients with those disorders.…”
Section: Kata Kunci: Periodontitis Keradangan Nf-κb P50 Nf-κb P65 mentioning
confidence: 99%